2018
DOI: 10.1016/j.jneb.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Knowledge, Attitudes, and Fruit and Vegetable Intake as Predictors of Head Start Teachers' Classroom Mealtime Behaviors

Abstract: There was limited support for associations among teacher knowledge, attitudes, and fruit/vegetable intake, and teacher classroom mealtime behavior. Findings showed that teacher mealtime behavior was significantly associated with teacher experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The proportion of providers meeting recommendations for fruit and vegetable consumption (3.5 cups or 5 servings per day) varied from 22.5% of Head Start staff [17] to 50% of family child care (FCC) providers [32]. Mean fruit and vegetable consumption exceeded recommendations in one study of Head Start teachers [16] but were below recommendations in one study of child care center (CCC) directors and staff [9].…”
Section: Diet Qualitymentioning
confidence: 96%
See 1 more Smart Citation
“…The proportion of providers meeting recommendations for fruit and vegetable consumption (3.5 cups or 5 servings per day) varied from 22.5% of Head Start staff [17] to 50% of family child care (FCC) providers [32]. Mean fruit and vegetable consumption exceeded recommendations in one study of Head Start teachers [16] but were below recommendations in one study of child care center (CCC) directors and staff [9].…”
Section: Diet Qualitymentioning
confidence: 96%
“…Among the five analyses of HS staff, one study found an average Center for Epidemiologic Studies-Depression (Scale) (CES-D) of 10.8 (at or above 16 is considered screening positive for depression) [12]; another found 35% of respondents with at least moderate depression at two time points during the year [18]; and Ling found that 31% of HS teachers were experiencing depressive symptoms [22]. In two analyses from the Pennsylvania Head Start Survey [33,34], approximately 24% of respondents had a CES-D score at or above 16. This contrasts with only 17.6% of a national comparison sample with similar demographics.…”
Section: Depressionmentioning
confidence: 99%
“…Childcare educators are important role models given the length of time children spend in care, and can aid the development of a child through play based learning, social interaction, school readiness, and food practices [30,42,43], as well as enhance behaviours learned at home [23]. Beyond modelling, a childcare educator's unique personal values, beliefs and perceptions, age, education level, ethnicity, health status, length of employment in childcare and training can also impact their behaviours and practices with children in their care [14,34,[44][45][46][47][48][49]. While Australian childcare educators are required to have a minimum of a Certificate lll in Early Childhood Education and Care [22], Australian studies [50,51] show that childcare educator nutrition knowledge varies greatly, and personal experiences mostly shape attitudes and practices [52].…”
Section: Introductionmentioning
confidence: 99%
“…A first step for providing this support is to accurately identify knowledge deficits, in which using a valid and reliable ECEC teacher nutrition and physical activity knowledge questionnaire is useful. The current range of ECEC teacher nutrition and physical activity knowledge questionnaires that demonstrate at least construct and content validity are relatively out-of-date (ranging from 1972-2010) [9][10][11][12], mostly related to US teachers [9][10][11][12][13][14][15][16][17][18][19][20], and/or often include content that is not specific to pre-schoolers' nutrition nor physical activity [11,17,18,21]. Other knowledge questionnaires focusing on the diet of young children have been used to assess parental knowledge, but these are limited in scope, lack validity, and feature items that are overly specialised, for example, asking parents to decide if the following statement is correct: "If one should pay attention to the weight of a pre-schooler, it is preferable to substitute potatoes by rice and pasta" [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Other knowledge questionnaires focusing on the diet of young children have been used to assess parental knowledge, but these are limited in scope, lack validity, and feature items that are overly specialised, for example, asking parents to decide if the following statement is correct: "If one should pay attention to the weight of a pre-schooler, it is preferable to substitute potatoes by rice and pasta" [22,23]. Through a semi-structured literature review of caregivers' nutrition knowledge, we identified only four [9,10,12,24] of 15 studies used nutrition/physical activity knowledge questionnaires that showed content and construct validity; four were partially validated (no construct validity) [16,19,20,25], and the remaining seven [13][14][15]17,18,21,26] either did not describe validation methods or did not appear to be validated. These characteristics may have limited the quality of evidence for ECEC teachers' nutrition knowledge.…”
Section: Introductionmentioning
confidence: 99%